Climate Change, Ecology and Systematics - Hodkinson, Trevor R.; Jones, Michael B.; Waldren, Stephen; Parnell, John A. N. (Cambridge : Cambridge University Press, 2011)
Climate change has shaped life in the past and will continue to do so in the future. Understanding the interactions between climate and biodiversity is a complex challenge to science. With contributions from 60 key researchers, this book examines the ongoing impact of climate change on the ecology and diversity of life on earth. It discusses the latest research within the fields of ecology and systematics, highlighting the increasing integration of their approaches and methods. Topics covered include the influence of climate change on evolutionary and ecological processes such as adaptation, migration, speciation and extinction, and the role of these processes in determining the diversity and biogeographic distribution of species and their populations. This book ultimately illustrates the necessity for global conservation actions to mitigate the effects of climate change in a world that is already undergoing a biodiversity crisis of unprecedented scale.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Climatic changes